Association of Age with Metabolic Biomarkers and Insulin Resistance in Patients with Type 2 Diabetes in Basrah, Iraq - Mohammed Adil Abdulhassan; Shurok Namah khudair; Khairallah A.S Mohammed; Abdulaziz Qadori Abdulsada (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Type 2 diabetes mellitus (T2DM) is an age-related metabolic disorder characterized by progressive metabolic deterioration. Specific Background: Orexin-A and cathepsin-D have been implicated in hypothalamic regulation and cellular quality control, yet their age-related alterations in T2DM remain insufficiently characterized. Knowledge Gap: The interplay between aging, hypothalamic dysfunction, and cellular stress markers in relation to insulin resistance has not been comprehensively explored. Aims: This study investigated age-associated changes in orexin-A and cathepsin-D and their correlations with insulin resistance in T2DM patients. Results: A cross-sectional analysis of 110 T2DM patients and 70 controls revealed a significant age-related decline in orexin-A levels (69% reduction, p=0.001) and an increase in cathepsin-D levels (p=0.005). Orexin-A showed a negative correlation with insulin resistance (r = -0.26, p = 0.005), whereas age and cathepsin-D were positively correlated with HOMA-IR. Traditional metabolic markers, including HbA1c, triglycerides, and LDL, worsened with age. Regression analysis identified age, BMI, and cathepsin-D as positive predictors, while orexin-A was a negative predictor of insulin resistance. Novelty: This study identifies a previously unreported relationship between declining orexin-A and increasing cathepsin-D levels as age progresses in T2DM. Implications: These findings highlight the relevance of age-specific metabolic pathways and suggest the need for tailored therapeutic approaches in older diabetic populations. Highlights:• Progressive reduction of orexin-A observed across advancing age groups• Increasing cathepsin-D levels linked to worsening metabolic profiles• Age and biomarker patterns associated with higher insulin resistance Keywords: Type 2 Diabetes Mellitus, Aging, Orexin-A, Cathepsin-D, Insulin Resistance